Motor competence interventions in children and adolescents - theoretical and atheoretical approaches: A systematic review - Khodaverdi, Z.; O`Brien, W.; Duncan, M.; Clark, C. C. T. (Journal of Sports Sciences, 2022)
This study aimed to compare for the first time the immediate and retention effects of theory-based and atheoretical motor competence (MC) interventions, by conducting a systematic review to determine which intervention approach resulted in the most improvements for motor outcomes. In accordance with PRISMA guidelines, studies were identified from searches across seven databases, for articles relating to theory-based (Achievement Goal Theory, Dynamic Systems Theory, and Social-Cognitive Theory) and atheoretically-derived MC interventions in typically developing children and adolescents. Publication bias was assessed using an adapted form of Consolidated Standards of Reporting Trials statement. Of the thirty two included studies, seventeen utilized theory-based intervention approaches. The majority of studies were grounded in Achievement Goal Theory. Also, the majority of MC interventions elicited immediate (short) and/or long-term effects for children and adolescents. Studies varied with regards to intervention components and MC assessment. Many studies scored poorly for risk of bias items. Overall, the levels of success for theoretical and atheoretical intervention programmes were not distinguishable. Findings open up new horizons for motor skills instruction to be taught using developmentally appropriate pedagogy, a research field which has gained significant traction among stakeholders in recent years.